(untitled) (Computer systems and information technologies, 2025)
In this paper, the author presents a simple and efficient C++ thread pool implementation capable of executing task graphs. The conducted experiments demonstrate that the proposed solution achieves CPU performance comparable to Taskflow, a highly optimized library for parallel and heterogeneous programming. The implementation is small and straightforward, consisting of less than one thousand lines of C++ code at the time of writing this paper.